Pengaruh Konflik Terhadap Kinerja Karyawan Pada PT. Pegadaian (Persero) Manado - Andri Ramadhan Walangantu; Harry J. Sumampouw; Henny S. Taroreh (JURNAL ADMINISTRASI BISNIS, 2018)
Conflict comes from the Latin verb configere which means to hit each other. Sociologically, conflict is defined as a social process between two or more people (or groups) where one party attempts to remove the other by destroying it or making it powerless. The purpose of this study is to determine the effect of conflicts that occur in the performance of employees at PT. Pegadaian (Persero) Manado samples taken as many as 30 respondents. Data collection methods used are questionnaires, interviews, and documentation. Data were analyzed using descriptive research method of research that is research which combine between qualitative and quantitative method. In this research, the result of simple correlation shows strong correlation or influence between conflict variable and performance equal to 0,87% and based on that calculation hence sought the amount of contribution of conflict to performance with result of 75,69%. And in this research the authors get the result of conflict impact terhadapa employee performance that has a positive impact. The conclusion of this research result shows the reality of Manado Pegadaian employees handling and managing employees conflicts done efficiently and effectively then positive impact will arise through the behavior that is seen by employees as potential human resources with various consequences such as improving order, discipline in using work time, increasing productive cooperative relationship, work motivation. And suggestions to try to improve or sustain the application of existing conflicts through the application of a conscious presence of role conflict, accepting the conditions and stressful situations in work caused by the conflict, trying to be able to tolerate conflict, will have an impact on the improvement of employee performance.Â Keywords : Conflict, Employee Performance